2018
DOI: 10.1021/acs.langmuir.8b02584
|View full text |Cite
|
Sign up to set email alerts
|

Diblock Polymer Brush (PHEAA-b-PFMA): Microphase Separation Behavior and Anti-Protein Adsorption Performance

Abstract: In this paper, a series of amphiphilic diblock polymers of poly(hydroxyethylacrylamide)- b-poly(1H,1H-pentafluoropropyl methacrylate) (PHEAA- b-PFMA) were grafted from silicon wafer via surface-initiated atom transfer radical polymerization (SI-ATRP). Surface wettability and chemical compositions of the modified surfaces were characterized by contact angle goniometer and X-ray photoelectron spectroscopy (XPS) respectively. Molecular weight and polydispersity of each block were measured using gel permeation chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…Figure b shows the XRD patterns of MoO 3 , MoO 3 ‐GO, and GO. From Figure b, it can be seen that all characteristic peaks of MoO 3 are attributed to α‐MoO 3 . The observed three strong diffraction peaks of MoO 3 at about 13.1°, 26.1°, and 39.2° can be assigned to (020), (040), and (060) plane, respectively, which suggest a high crystallinity of the nanostructures.…”
Section: Resultsmentioning
confidence: 90%
“…Figure b shows the XRD patterns of MoO 3 , MoO 3 ‐GO, and GO. From Figure b, it can be seen that all characteristic peaks of MoO 3 are attributed to α‐MoO 3 . The observed three strong diffraction peaks of MoO 3 at about 13.1°, 26.1°, and 39.2° can be assigned to (020), (040), and (060) plane, respectively, which suggest a high crystallinity of the nanostructures.…”
Section: Resultsmentioning
confidence: 90%
“…These results showed that the surface‐initiated SET‐RAFT polymerization of HEAAm on the silicon surface proceeded uniformly for the emergence of a moderately grafted poly(HEAAm) layer. Surface‐initiated ATRP of HEAAm had been previously reported by Liu and co‐workers from the surface of gold with goal of anti‐protein adsorption performance, but the water contact angle of poly(HEAAm) was about 9 o due to the presence of bromine atoms (Br) at the end of polymer brush (Poly(HEAAm‐Br)) and this value was not useful for anti‐protein adsorption. Therefore, they also synthesized an amphiphilic diblock polymer brush of poly(hydroxyethylacrylamide)‐b‐poly(1H,1Hpentafluoropropylmethacrylate) (Si‐Poly(HEAAm)‐b‐Poly(FMA)) at 110 °C in oil bath.…”
Section: Resultsmentioning
confidence: 99%
“…HEAAm monomer contains two hydrogen‐bond donors such as hydroxyl group and amide group in the backbone. In this case, poly(HEAAm) is expected to exhibit good antifouling ability due to the hydrogen‐bond donors enhancing surface hydration as indicated by low water contact angles (e.g., 9 o –34 o ) . Thus, poly(HEAAm) brushes may be used as promising biomaterials with long‐term biocompatibility and durability suitable for applications in complex biological media.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly interesting are the techniques of reversible-deactivation radical polymerization (RDRP), allowing the control of the density and length of surface-grafted macromolecules at the same time leading to the formation of complex polymer brush architectures, rising from the initiation site attached to the surface according to the grafting from approach [6][7][8][9][10]. The grafting from method uses the presence of a polymerization initiator connected by a covalent bond to the surface enabling the formation of polymer chains on previously functionalized substrates [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%